Groundwater salinity and its effect on elevated concentrations of other contaminants in a coastal plain: a perspective for infrastructure protection. Issue 1 (1st July 2022) - Rusydi, A F; Onodera, S-I; Ioka, S; Maria, R; Firmansyah, F; Saito, M; Purwoko, W; Sukmayadi, D
Abstract: Salinization is a serious threat to coastal groundwater because it degrades water quality and results in trace metal dissolution. Meanwhile, groundwater quality is critical for human and development, as contaminated groundwater cause a negative effect on human`s health and infrastructure. Our investigation of a specific area, Indramayu, on West Java's north coast revealed that most groundwater samples are brackish to saline in existence. TDS concentrations in groundwater samples were predominantly in the >1, 000 to nearly 30, 000 mg/L range. Concentration contours were disproportionately high in the north tip area. Numerous factors contribute to the high salinity of this area, including the interaction of saline water and sediment with low-salinity groundwater and evaporation. Additionally, high TDS levels were significantly correlated with Fe 2+ and Mn 2+ concentrations ( p < 0.001). The area's high salinity was thought to facilitate the dissolution of trace metals from minerals such as siderite and rhodochrosite (SI of the minerals > 1). Concentrations of Fe 2+ and Mn 2+ were very likely to damage the water piping system. In terms of water quality, less than 30% of samples were fit for human consumption. Finally, the government should take into account the groundwater environment when developing the area in order to protect human health and infrastructure.